ENVIRONMENTAL IMPACT CAUSED BY INCORRECT DISCARD OF TIRES - Silva Alves, Vitoria Emanuella da [UNESP]; Vasconcelos, Guilherme Malta; Moreira, Rafael Nascimento; Alves Filho, Moacir de Jesus; Barreto, Thassiane da Silva (Fac Eniac, 2016)
Tires are wastes that need special treatment, because when buried whole, its shape facilitates the accumulation of gases from the decomposition of other waste and in case of emerge surface provides shelter for diseases. Thus, this research aimed to provide information about the environmental impacts caused by the improper disposal of unserviceable tires and about some techniques for reusing and recycling them. We opted for the literature search using databases SCIELO, Google Scholar, CAPES journals, resolutions of the MMA, the ANIP and regulations of IBAMA instructions. The consultation material comprises a period from 1992 to 2015 with the following descriptors: industrial waste; laws of tires; environmental impacts caused by improper disposal of tires and technological alternatives usable by tires and scrap therefore improper disposal of scrap tires can cause negative impacts such as floods, by reducing the flow capacity of water bodies and drains. In contrast, after use, the tire can undergo reform and be reused, but the wear out is completely characterized as waste tire and the correct disposal are the possible ways of recycling. Thus it is very important compliance of laws that deal with the proper disposal of tires.
Keywords: Improper disposal; Unserviceable tires; Solid wast